Diverse Emperor Penguin Algorithm for Partially Shaded PV Array Reconfiguration - Marneni, Anil; Murugesan, Pravin; Chandrasekharan, Sowthily; Paramasivam, Muhilan; Subramaniam, Senthil Kumar (Periodica polytechnica. Electrical engineering and computer science, 2025)
A significant challenge in the operation of Photo-Voltaic (PV) array is partial shading, which drastically reduces the power output. Shaded arrays exhibit numerous local Maximum Power Point (LMPP) alongside a single Global Maximum Power (GMP). Reconfiguring shaded modules to extract the GMP is crucial, and achieving this relies heavily on a uniform shadow distribution across the PV surface. This paper proposes a novel strategy, Diverse Emperor Penguin (DEP) algorithm, for uniform shadow distribution across shaded PV arrays. It is a onetime static reconfiguration technique based on the commonly occurring shading patterns in a given location. The proposed strategy was tested on 9 × 9 PV array at ten distinct shading patterns in MATLAB/Simulink platform. The analytical results observe the power enhancement at all the shading patterns and highest power improvement is 23.01%, 10.20% when compared with standard TCT and SuDoKu configurations respectively. The same were tested experimentally on 3 × 3 PV array and compared with standard TCT and SuDoKu configurations and the results obtaind confirm that the proposed technique has superior performance compared with stated techniques.